2015
DOI: 10.1080/2162402x.2015.1052213
|View full text |Cite
|
Sign up to set email alerts
|

Non-classical HLA-class I expression in serous ovarian carcinoma: Correlation with the HLA-genotype, tumor infiltrating immune cells and prognosis

Abstract: In our previous studies, we have shown that patients with serous ovarian carcinoma in advanced surgical stage disease have a particularly poor prognosis if they carry the HLA-A*02 genotype. This represent a stronger prognostic factor than loss or downregulation of the MHC class I heavy chain (HC) on tumor cells. In this study, we investigated the expression of the non-classical, immune tolerogenic HLA -G and -E on the tumor cells along with the infiltration of immune cells in the tumor microenvironment. FFPE p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 57 publications
2
47
0
Order By: Relevance
“…We and others reported a negative correlation of HLA-E on the overall survival of cancer patients (Talebian Yazdi et al, 2016, Gooden et al, 2011, van Esch et al, 2014, Seliger et al, 2016, Andersson et al, 2016, Silva et al, 2011); in particular, the beneficial effect of high CD8 T cell counts within tumor was mitigated by high protein expression of HLA-E (Talebian Yazdi et al, 2016, Gooden et al, 2011). These findings suggested that NKG2A receptor expression on tumor-infiltrating lymphocytes might hamper their function by interaction with HLA-E in the microenvironment.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…We and others reported a negative correlation of HLA-E on the overall survival of cancer patients (Talebian Yazdi et al, 2016, Gooden et al, 2011, van Esch et al, 2014, Seliger et al, 2016, Andersson et al, 2016, Silva et al, 2011); in particular, the beneficial effect of high CD8 T cell counts within tumor was mitigated by high protein expression of HLA-E (Talebian Yazdi et al, 2016, Gooden et al, 2011). These findings suggested that NKG2A receptor expression on tumor-infiltrating lymphocytes might hamper their function by interaction with HLA-E in the microenvironment.…”
Section: Introductionmentioning
confidence: 66%
“…HLA-E is ubiquitously expressed at low levels, but very high expression can be found on trophoblasts and ductal epithelial cells in immune-privileged tissues like placenta and testis, respectively. In cancers, HLA-E is frequently overexpressed compared to their non-transformed counterparts, including melanoma and carcinomas of lung, cervix, ovarium, vulva and head/neck (Talebian Yazdi et al, 2016, Gooden et al, 2011, van Esch et al, 2014, Seliger et al, 2016, Andersson et al, 2016, Silva et al, 2011). The physiological function of HLA-E is to present ‘self’ peptides derived from other HLA class I molecules (DeCloux et al, 1997, Kraft et al, 2000, O’Callaghan et al, 1998) and to limit autoimmune reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…Stabilized by peptide loading (24), the HLA-E/peptide complex dampens initial NK cell responses by binding CD94/NKG2A. HLA-E is indeed overexpressed in several tumors (25)(26)(27)(28)(29)(30)(31)(32)(33), and a correlation between higher HLA-E and poorer prognosis has been observed (25,27). Moreover, NKG2A + NK cells are reportedly predominant in the tumor microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…Aberrant expression of HLA genes has been identified in many human cancers. For instance, overexpression of HLA-G (subtype of HLA class I) has been demonstrated in various human malignancies, such as melanoma, breast cancer, and ovarian cancer [14][15][16][17]. Moreover, correlation of HLA-G overexpression with poor prognosis in low-grade gliomas (LGGs) has also been demonstrated previously by our group [18].…”
Section: Introductionmentioning
confidence: 79%